Engineering of Droplet Charges in Microfluidic Chips. Issue 4 (12th February 2020) - He, Rongxiang; Ruan, Meilin; Qi, Yuyang; Liu, Hongni; Zhang, Zhengtao; Chen, Chaohui; Chao, Yiping; Liu, Yumin; Chen, Yong
Abstract : Droplet‐based technologies, which utilize the surface charge characterization of droplets, are used in fluorescence‐activated cell sorting and energy harvesting. Herein, the influence of droplet charges on microchips is investigated via surface engineering. An electrical field is applied to deflect the droplets in a microchannel, thereby enabling a qualitative analysis of the droplet charge. In a glass polydimethylsiloxane (PDMS)‐boned microchip, the droplet charge decreases when the microchannel is changed from a single‐sided to a three‐sided rectangular microstructure. When the ionic concentration of the droplet increases from 1 μm to 10 mm, droplet charges decrease by ≈78%. Meanwhile, a Au film is patterned in the microchannel, and 11‐aminoundecanethiol hydrochloride (AUT) and 12‐mercaptododecanoic acid (MDA) are modified to modulate the Au surface characterization. Compared with the glass–PDMS‐bonded microchannel, the Au film can suppress the streaming potential to decrease the droplet charges. After modification with MDA and AUT, the droplet charges increase. Therefore, the microchannel structures, ionic concentration, and substrate surface properties can be utilized to modulate the droplet charges, which can be widely used in droplet‐based energy harvesting and biological and chemical sample sorting. Abstract : In this study, surface engineering in microfluidic chips is used to modulate droplet charges. After changing the microchannel structures and surface characterization, droplet charges change responsively. Droplets with high ionic concentration have low charges. This study provides a powerful tool for droplet‐based cell sorting or energy harvesting.